Barbados : Third Review Under the Extended Arrangement, Requests for Augmentation of Access, and Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Barbados. (IMF Staff Country Reports; Country Report ;, 2020)
This paper focuses on Barbados' Third Review Under the Extended Arrangement, Requests for Augmentation of Access, and Modification of Performance Criteria. Barbados continues its strong implementation of the comprehensive Economic Recovery and Transformation plan aimed at restoring fiscal and debt sustainability and increasing reserves and growth. The ongoing global coronavirus pandemic poses a major challenge for the economy, which is heavily dependent on tourism, and is expected to have a large impact on the balance of payments and the fiscal accounts. State-owned enterprise (SOE) reform remains an essential element of Barbados' economic program. In order to secure fiscal space for investment in physical and human capital, transfers to SOEs need to decline after the global coronavirus pandemic with a combination of stronger oversight of SOEs, cost reduction, revenue enhancement, and mergers and divestment. Progress in restoring fiscal sustainability must be safeguarded by adopting a new central bank law that limits its financing of the Government to short-term advances and strengthens the central bank's mandate, autonomy, and decision-making structures. A strong recovery after the global pandemic will depend on accelerating structural reforms. There is much room for improvement in the business climate. Establishing a credit registry and credit collateral registry, in addition to broadening the types of eligible collateral, would facilitate access to credit.